2019
DOI: 10.24875/ciru.18000052
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculitis asociada a drenaje extraventricular: etiología, diagnóstico y tratamiento enfocado a unidades de cuidados neurocríticos

Abstract: La ventriculitis posterior a un drenaje extraventicular constituye una complicación neuroquirúrgica muy importante en las unidades de cuidados neurocríticos. Se hace necesario realizar un diagnóstico precoz, dado que la morbimortalidad secundaria a esta puede ser variable y complicar la evolución de los pacientes neurocríticos. A pesar de esto, la ventriculostomía continúa siendo un pilar importante en el monitoreo y el tratamiento. Ante la urgencia de ventriculitis asociadas a gérmenes multirresistentes han s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…EVD-associated CNSIs are prone to more complicated infections as well as other complications, which may have contributed to this result. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVD-associated CNSIs are prone to more complicated infections as well as other complications, which may have contributed to this result. 20 …”
Section: Discussionmentioning
confidence: 99%
“…CNSIs are prone to more complicated infections as well as other complications, which may have contributed to this result. 20 FUCC positivity is defined as Persistent Gram-negative bacterial meningitis/encephalitis in this study. The Cox proportional hazard analysis using propensity score weighting revealed that FUCC positivity was not a predictor of mortality, which may be due to the insufficient sample size.…”
mentioning
confidence: 99%
“…The incidence of EVD-related infection after neurosurgery ranges from 8% to 22%. Therefore, attention should be given to the clinical application of drainage tubes, and the removal indication should be evaluated as early as possible [ [37] , [38] , [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%